The influence of variation milling time into mechanical properties for 5% SiC reinforced P/M 5082 develop by using Powder Metallurgy technique - Ade, Firdianto; Darwin, Sebayang; Shahruddin, Mahzan; Nozie, Abdullah; Noashida, Arsat; A.E.B., Ismail (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.